2017
DOI: 10.1097/bot.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

The Hip Fracture Patient on Warfarin: Evaluating Blood Loss and Time to Surgery

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Studies investigating hip fracture treatment and the use of anticoagulants have so far reported conflicting results. While increased risk of complications was detected in one study [ 18 ], other studies discovered no such effect [ 19 , 20 ]. These diverse findings could be explained by different perioperative administration of anticoagulant drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating hip fracture treatment and the use of anticoagulants have so far reported conflicting results. While increased risk of complications was detected in one study [ 18 ], other studies discovered no such effect [ 19 , 20 ]. These diverse findings could be explained by different perioperative administration of anticoagulant drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006 Foss et al [ 6 ] found that the median calculated total peri-operative blood loss in patients that had undergone intramedullary nailing was increased compared to patients that were operated with arthroplasty due to a hip fracture (1.86 L versus 1.30 L, respectively). Similarly, in a recent study by Cohn et al in 2017 [ 28 ] they found significantly lower preoperative Hb in patients undergoing intra medullary nailing (extra-capsular fractures) and a greater blood loss in the warfarin group compared with a control group (1.22 L versus 1.19 L) but this was not statistically significant. In contrast we found no difference in the calculated blood-loss when comparing warfarin patients with the control patients.…”
Section: Discussionmentioning
confidence: 88%
“…Cohn et al in their study showed that 58.1% of the patients in warfarin underwent transfusion after surgery comparing to a 56.6% in the control group ( p = 0.86). Also, the blood loss was similar in the two groups ( p = 0.95) [33]. Even Lott et al in their study of 479 patients with PFF, in which 112 were in therapy with warfarin, did not notice statistical differences in the two groups in terms of blood loss ( p = 0.35) and post-operative transfusions ( p = 0.535) [34].…”
Section: Discussionmentioning
confidence: 99%